PENGEMBANGAN MODEL EVALUASI KULTUR SMA - Siswanto, Siswanto (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2013)
Penelitian ini bertujuan untuk 1) mengindentifikasi, 2) me-ngembangkan model evaluasi, dan 3) mengetahui kelayakan model evaluasi kultur SMA yang dikembangkan. Penelitian ini merupakan penelitian dan pengembangan. Langkah-langkah penelitian dan pe-ngembangan menggunakan acuan pokok dari Plomp, sedangkan penentuan jumlah subjek uji coba menggunakan acuan dari Borg & Gall. Hasil penelitian menunjukkan bahwa 1) keadaan kultur akademik yang berkembang di SMA saat ini terdiri atas enam aspek budaya, yaitu berprestasi dan berkompetisi, disiplin dan efisien, jujur dan terbuka, gemar membaca, teguran dan penghargaan, serta kerja sama dan kebersamaan; 2) keadaan kultur sosial yang ber-kembang di SMA saat ini terdiri atas sembilan aspek budaya, yaitu jujur dan terbuka, teguran dan penghargaan, kerjasama dan keber-samaan, saling menghormati, bersih, disiplin dan efisien, ber-sahabat/komunikatif, saling percaya, dan semangat kebangsaan; 3) hasil confirmatory factor analysis (CFA) menunjukkan bahwa model evaluasi kultur akademik dengan responden siswa dan guru sesuai dengan data lapangan dan model evaluasi kultur SMA yang di-kembangkan layak digunakan.Kata kunci: pengembangan model, evaluasi, kultur sekolah______________________________________________________________DEVELOPING A MODEL OF AN EVALUATION OF THE SCHOOL CULTURE IN SENIOR HIGH SCHOOLSAbstract This study aims to: 1) identify the condition of the school culture in senior high schools (SHSs) at this moment; 2) develop a model of an evaluation of the school culture in SHSs; and 3) know the feasability of the developed model of the evaluation of the school culture in SHSs. This research was a research and development. This steps of the research and development were those proposed by Plomp, while the number of the try out subjects was established using Borg & Gall. The conclusions of the study are as follows 1) the condition of academic culture which is developing in SHSs consists of six cultural aspects, namely achievement and competition, discipline and efficiency, honesty and openness, reading habit, reward and punishment, and cooperation and togetherness; 2) the condition of social culture which is developing in SHSs consists of nine cultural aspects, namely honesty and openness, reward and punishment, cooperation and togetherness, mutual respect, cleanness, discipline and efficiency, friendliness/communicativeness, mutual trust, and nationalism spirit; 3) the result of the CFA shows that the evaluation model for the academic culture for the students is relevant to the field. Teacher respondance shows that value of KMO is 0,655; 4) the result of the social culture for students is relevant to the field. Teacher respondance shows that value of KMO is 0,682; 5) the effectiveness of the model of the evaluation of the school culture is judged as a good evaluation model.Keywords: model development, evaluation, school culture